2021
DOI: 10.1002/ptr.7112
|View full text |Cite
|
Sign up to set email alerts
|

Psidium L. genus: A review on its chemical characterization, preclinical and clinical studies

Abstract: The Myrtaceae family is considered one of the largest known botanical families and the genus Psidium is among the most economically interesting. Psidium genus comprises approximately 112 species, and it has been extensively studied, mainly because of Psidium guavaja species. Phytochemical investigations confirmed the presence of phenolics as the main compounds, as well as the essential oils, which were also widely investigated. Pharmacological studies report analgesic, anthelminthic, acaricidal, antihiperglice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…To date, species of the family Myrtaceae are among the recognized plants that provide many valuable products including EOs ( Arain et al, 2019 ). Notably, Psidium is one of the economically important genera because of its distinguished edible, essential oil-rich species such as P. guajava L. and P. cattleianum Sabine ( Beltrame et al, 2021 ). P. cattleianum Sabine is a Brazilian native shrub, where it is commonly known as “araçá” ( Faleiro et al, 2016 ); however, it is cultivated through the tropics and subtropics for its juicy, purple-red fruits known as strawberry guava or Cattley guava ( Patel, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, species of the family Myrtaceae are among the recognized plants that provide many valuable products including EOs ( Arain et al, 2019 ). Notably, Psidium is one of the economically important genera because of its distinguished edible, essential oil-rich species such as P. guajava L. and P. cattleianum Sabine ( Beltrame et al, 2021 ). P. cattleianum Sabine is a Brazilian native shrub, where it is commonly known as “araçá” ( Faleiro et al, 2016 ); however, it is cultivated through the tropics and subtropics for its juicy, purple-red fruits known as strawberry guava or Cattley guava ( Patel, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…There have been several reports concerning the biological activities of different Pisidium species [36]. For example, de Souza Cardoso et al (2018) reported the antidiabetic effects of phenolic compounds, especially anthocyanins in P. cattleyanum fruits [37].…”
Section: Introductionmentioning
confidence: 99%